Noncanonical Translation Initiation in Eukaryotes - Kwan, Thaddaeus (Cold Spring Harb Perspect Biol, 2019)
The vast majority of eukaryotic messenger RNAs (mRNAs) initiate translation through a canonical, cap-dependent mechanism requiring a free 5′ end and 5′ cap and several initiation factors to form a translationally active ribosome. Stresses such as hypoxia, apoptosis, starvation, and viral infection down-regulate cap-dependent translation during which alternative mechanisms of translation initiation prevail to express proteins required to cope with the stress, or to produce viral proteins. The diversity of noncanonical initiation mechanisms encompasses a broad range of strategies and cellular cofactors. Herein, we provide an overview and, whenever possible, a mechanistic understanding of the various noncanonical mechanisms of initiation used by cells and viruses. Despite many unanswered questions, recent advances have propelled our understanding of the scope, diversity, and mechanisms of alternative initiation.